The Contemporary Value of Marx’s Thought of "Real Individual" - Qi, Siwen (Journal of Global Economy, Business and Finance, 2024)
Looking at the development of Marxist philosophy, the idea of "real individual" is not achieved overnight, but a gradual and dynamic process, which has undergone the evolution of germination, formation and deepening. In the contemporary perspective, clarifying Marx's idea of "real individual" has important practical value in caring about the development of contemporary Chinese society. It helps us to base ourselves on "real individuals" and adhere to the development idea of "people-centered"; it helps to overcome the one-sided development of people and move towards the free and comprehensive development of people; it helps to point out the direction for the development of human society and build a community with a shared future for mankind.